(untitled) (Research, Society and Development, 2022)
Diabetes Mellitus (DM) is a pancreatic metabolic disease 1, which is the juvenile disease, being a predominant type of diabetes in the population, or a disease that has more prevalence in the least, and gestational diabetes, the fastest growing chronic condition in Brazil today. and in the world, with a worldwide mortality rate of 10.7%. The objective was to describe how the disease of onset will develop and especially the best-developed laboratory diagnostic methods for the onset of the disease early in the treatment, as well as the onset of the disease, macro and microvascular, with the beginning of the study by DM. This is an integrative literature review, where a research is based on electronic data and through the analysis of scientific articles and book material. They were used as inclusion criteria, published in the period from 2016 to 2021 and in Portuguese and English. After the selection process 2,224 articles using filters and inclusion criteria and selection of inclusion and selection of articles that were used to compose the results table, with different approaches on the topic addressed. Difficulties and advantages that possible tests, especially for practical and practical studies of DM, have been described as difficulties and advantages, especially for practical and practical studies, proven through the practical and practical means that can be performed for the diagnosis of DM. DM tracking.